2019
DOI: 10.1111/hdi.12717
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about medicines in dialysis patients and after renal transplantation

Abstract: Introduction: Patients with end‐stage renal disease are burdened by a complex medication regimen, but little is known about the belief about medicine among dialysis‐ and renal transplant (RTX) patients. Patients’ beliefs about medicines may influence drug adherence and thereby affect morbidity and mortality. The aim of the present study was to assess the beliefs about medicine in dialysis as well as after RTX. Methods: In a prospective study, 301 dialysis patients were followed for up to 5.5 years during which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Results also indicated that adolescents in this sample perceived the benefits of their medications to outweigh the consequences, similar to previous findings. 26,28 This suggests that adolescents may understand and accept the necessity of taking their prescribed medications post-transplant but that their transplant-specific HRQOL is affected by other considerations such as concerns about long-term overuse and potential harm of the transplant regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results also indicated that adolescents in this sample perceived the benefits of their medications to outweigh the consequences, similar to previous findings. 26,28 This suggests that adolescents may understand and accept the necessity of taking their prescribed medications post-transplant but that their transplant-specific HRQOL is affected by other considerations such as concerns about long-term overuse and potential harm of the transplant regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, younger adolescents expressed greater concerns about medications than older adolescents, with stronger beliefs about the harmfulness of their medications 25 . Among adults on dialysis and kidney transplant, 34.4% reported strong concerns about their medications (eg, long‐term effects, dependence) and 17.3% believed their medications to be harmful, while the majority (98.2%) strongly believed their medications to be necessary for their physical well‐being 26 . Patient beliefs that medication is necessary was related to better adherence in dialysis patients 27 while lower perceived benefits, perceived harmfulness, and greater concerns about medication were associated with lower adherence in transplant samples 28‐30 .…”
Section: Beliefs About Medicinementioning
confidence: 95%
See 1 more Smart Citation
“…Besides that, PHR users who had a negative opinion about the PHR and/or had a suggestion to improve the PHR were potentially more motivated to participate in this study which may have caused inclusion bias. Furthermore, Marien et al included patients with pulmonary transplants who have potentially a higher perceived usefulness of their (live saving) drugs compared to our study sample [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle ilaç inancını etkileyen faktörleri belirlemek sağlık sonuçlarını iyileştirmek için çok önemlidir. Son yıllarda farklı ilaçlara karşı hastaların ilaç inancını inceleyen çalışmalarda; çoklu ilaç kullanımı, yaş, etnik köken, çevresel faktörler, hastanın hastalık ve tedavi ile ilgili inancı, düşüncesi ve bilgisi, gibi faktörlerin tedaviye uyum düzeyini etkileyebileceği ifade edilmiştir (16)(17)(18)(19). Bu faktörler arasında, hastaların ilaçlar hakkında inançları, ilaca uyum açısından güçlü bir faktör olarak değerlendirilmektedir.…”
unclassified